(untitled) - Benjamin, Jules R. (New York, 1987)
This is an introduction to the study of history for undergraduates. It aims to help students master basic concepts of the subject and to learn the skills they will need, from a description of what historians do and what kind of research they conduct, through notetaking in class, taking exams and doing research on their own. It also tells students how to read maps, charts and graphs. Appendices provide lists of basic resource for research and study, and include multicultural and multi-ethnic information, such as American Indian history, Puerto Rican history, women's history and African-American history.
Keywords: History; Study and teaching